In-situ studies into the characterisation and degradation of blue ballpoint inks by diffuse reflectance visible spectroscopy - Sauzier, G; Giles, Peter; Lewis, Simon; van Bronswijk, Wilhelm (R S C Publications, 2015)
35 blue ballpoint inks sourced from Western Australian retailers were deposited onto commercial copy paper and analysed using diffuse reflectance visible spectroscopy. Principal component analysis showed that while several pens were clearly distinguishable based on their visible spectra alone, others exhibited overlap. Linear discriminant analysis was then used to build a chemometric model for the classification of the inks. Using a separate validation set, 71.7% of spectra were correctly assigned to a specific pen, and a further 16.7% to the correct pen supplier. Analysis of six pen inks stored under different conditions found the inks remained chemically stable for at least two months when stored in the dark. However, two inks exhibited spectral changes within one week under ambient light, and all but one ink displayed changes within two months, resulting in altered predictions using the chemometric model. This may be useful in cases of alleged fraud, where it is suspected that an ink entry may have been altered using the same pen at a later date. Artificial ageing experiments found that both heat and ultraviolet light play a role in the ageing process, and that accelerated ageing using these factors gives a reasonable depiction of short-term ageing under natural conditions.